Determinan Niat Membayar Zakat Profesi pada Karyawan Swasta (Studi Kasus Muzakki Laznas Daarut Tauhiid Peduli) - Ujang Sadili (LPPM IAI Pangeran Dharma Kusuma Segeran Indramayu, 2026)
The potential for a high number of figures is the company's zakat value of Rp. 144.5 trillion (44%), then the potential total amount for professional zakat (income) and services is Rp. 139.07 trillion or 42%. BAZ, which was established, is an alternative solution to the large potential for zakat, including professional zakat. This private employee zakat potential, the researchers decided to examine what determinants or factors influence the intention to pay zakat income to private employees, with research respondents being muzakki who have already paid zakat through the national zakat institution DT Peduli, with the Theory of Planned Behavior approach Objectives: This study aims to identify and analyze the factors that affect the intention to pay zakat on private employees Design/methodology/approach – This research is a qualitative research using SEM- PLS with primary data taken from questionnaires based on convenience sampling, totaling 100 respondents. Findings: Religious figures and peers influence the subjective norms of private employees' intention to pay zakat. Perceptions of behavioral control on employee intention to pay zakat are influenced by zakat knowledge, zakat law enforcement, and the quality of zakat distribution. Attitudes, subjective norms, and perceptions of behavioral control directly influence employees' intentions to pay professional zakat.